2010
DOI: 10.1103/physrevlett.104.017001
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Stripelike Flux Patterns Obtained by Freezing Kinematic Vortices in a Superconducting Pb Film

Abstract: We demonstrate experimentally and theoretically that the dissipative state of superconducting samples with a periodic array of holes at high current densities consists of flux rivers resulting from a short-range attractive interaction between vortices. This dynamically induced vortex-vortex attraction results from the migration of quasiparticles out of the vortex core (kinematic vortices). We have directly visualized the formation of vortex chains by scanning Hall probe microscopy after freezing the dynamic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 25 publications
(20 reference statements)
2
56
0
Order By: Relevance
“…This particular case, with one of the principal axes coinciding with the Lorentz force, has been discussed in Ref. 17. Concerning the symmetry of the individual pinning motifs, by using a triangular symmetry we are able to demonstrate that, as we stated above, the details of the dynamic phases are influenced by the particular geometry of the holes.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…This particular case, with one of the principal axes coinciding with the Lorentz force, has been discussed in Ref. 17. Concerning the symmetry of the individual pinning motifs, by using a triangular symmetry we are able to demonstrate that, as we stated above, the details of the dynamic phases are influenced by the particular geometry of the holes.…”
Section: Discussionmentioning
confidence: 50%
“…This prediction has been indeed observed in many different superconducting materials, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] thus demonstrating the universal character of this phenomenon. According to the LO model, the current density J * and the voltage V * at the point where the instability is triggered, are uniquely defined.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…It has been already shown that, due to the periodicity of the lattice of ADs, magnetic flux can be channeled mainly along the [10] and the [01] directions of the lattice [29,30]. This is also true for thermomagnetic avalanches, where finger-like penetration consisting of a main trunk and small branches at 90 • , has been observed in Pb and Nb samples with square arrays of antidots [18,19].…”
Section: Resultsmentioning
confidence: 59%
“…17,18 The dissipative states of superconducting samples with a periodic array of holes were experimentally measured. 19,20 Special attention has also been paid to the rectification of vortex motion (ratchet effect) induced by asymmetric pinning potentials. [21][22][23][24][25][26] The effect of finite-size and temperature on vortex motion using the timedependent Ginzburg-Landau theory was reported.…”
Section: Introductionmentioning
confidence: 99%